Second branchial cleft anomalies: a review of 12 cases - Modi, Niral R.; Anadani, Jamin; Tota, Sanjay M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: It is a combined retrospective and prospective study of 12 cases of branchial cleft anomalies presented to our hospital. We analysed them for their age and sex incidence, side prevalence, according to clinical features and treatment outcomes. Methods: Thorough history was taken and examination was done and these cases are investigated with CT scan, MRI scan and treated with surgical excision. Results: Cyst is seen in 7 (58.33%) patients while one case of sinus and one (8.33%) of fistula,1 case of co-existing sinus and fistula (8.33%), and one Bilateral sinus and 1 bilateral fistula (8.33%) were seen. Overall incidences of branchial anomalies are more (40%) in 11-15 year age group. Overall incidence of branchial anomalies is more in male (66.66%) than female (33.33%). 4 cysts were right sided and 3 were left sided. Sinus and fistula were seen one case having right sided and 1 case having bilateral anomaly. Patients having branchial cysts presents most commonly with neck swelling and pain while patients having fistula and sinus presents commonly with discharging opening over anterior neck. 1 case of recurrence found in cyst on follow up and no recurrences were seen in sinus and fistula. Conclusions: Cyst is the most common anomaly, most commonly affected age group is 11-15 years, male are more commonly affected, these anomalies are more prevalent on right side, and there are very less chances of recurrence after surgical excision.